BRICS as New Alternatives in Reforming International Financial Institutions and Economic Partnerships - Aleksia, Casandra; Bakhtiar, Arief Rizky (Insignia: Journal of International Relations, 2023)
The article aims to examine the role of the combined economies of Brazil, Russia, India, China and South Africa (BRICS) in reforming the international financial institutions and economic partnerships. BRICS offers new values and serves as alternatives for both its current and prospective members in having an equal access to source international investments.. The arguments revolve around BRICS’ strategies to create an effective development program that not only revolves around their own growth agendas. In addition, BRICS have greater goals on establishing global trade relations and economic partnerships through the New Development Bank (NDB) and Contingent Reserve Arrangement (CRA) among many others. The discussion also focuses on other several key research areas related to BRICS’ efforts in promoting economic partnerships and the overall impacts of the partnerships. By emphasizing the shared interests of developing nations and emerging markets, giving high-quality economic and trade development priority, promoting true multilateralism, and highlighting opportunities in emerging fields to contribute more to an open global economy, this paper offers recommendations for BRICS’ future development. This study uses qualitative method to achieve the objectives of this study. The most fundamental characteristic of qualitative research is seeing the problems studied from the perspective of the subjects studied. Keywords: BRICS, economic cooperation, financial institution, partnership